TTK ve CMR'ye göre karayolu taşıma senedi - Tekin, Safa Murat (My University, 2024)
Taşıma sözleşmesinde yük taşıyıcıya teslim edilene kadar taşıyıcının, teslim edildikten sonra da gönderenin yük üzerinde hâkimiyeti bulunmaz. Bu nedenle tarafların, ispatı gereken vakıalarla ilgili delilleri toplaması genellikle zordur. Uygulamada taşıma sözleşmesinin çoğu zaman sözlü kuruluyor olması ispat faaliyetini daha da güçleştirmektedir. Bu zorluğu aşabilmenin en iyi yolu taşıma sözleşmesi kapsamında bir taşıma senedi düzenlenmesidir. Zira taşıma senedi içeriğinde bulunan kayıtlar sayesinde taşıma sözleşmesi ve yüke ilişkin ispat kolaylığı sağlar. Ayrıca taraflar yarar gördüğü hususları taşıma senedine kayıt olarak ekleyebilirler. Bu sayede diledikleri konuda taşıma senedinin ispat fonksiyonundan yararlanabilirler. Çalışmada öncelikle taşıma senedinin tanımı, hukuki niteliği ve taşımacılıkta kullanılan benzer belgelerden farkı ortaya koyulmuştur. Sonrasında taşıma senedinin içeriğinde yer alan kayıtlar teker teker incelenmiştir. Daha sonra ise taşıma senedinin ispat gücü detaylı olarak açıklanmıştır. Esasında yabancılık unsuru bulunan durumlarda ispat sorunları lex fori’ye tabi olmasına rağmen, uluslararası taşımalarda kullanılan taşıma senedinin ispat gücü hakkında özel ispat kuralları bulunmaktadır. Bu nedenle taşıma senedinin ispat gücü hem ulusal hem de uluslararası taşımalar açısından karşılaştırmalı olarak ele alınmıştır. Taşıma senedi ispat aracı olmasının yanı sıra taşıyıcı, gönderen ve gönderilen açısından bazı sorumluluklar da doğurabildiği için çalışmada taşıma senedinden kaynaklanan sorumluluklar üzerinde de durulmuştur.

In the contract of carriage, the carrier has no control over the goods until it is delivered to him and the sender has no control over the goods after it is delivered to the carrier. For this reason, it is often difficult for the parties to collect evidence regarding the facts that need to be proven. The fact that the transportation contract is often formed verbally in practice, makes it even more difficult to prove anything. The best way to overcome this difficulty is to issue a consignment note within the scope of the contract of carriage. Because the consignment note provides ease of proof through the particulars it contains regarding the contract of carriage and the goods. In addition, the parties may enter in the consignment note any other particulars which they may deem useful. This way, they can benefit from the proof function of the consignment note on any subject they wish. First in the study, the definition of the consignment note, its legal nature and its difference from similar documents used in transportation are explained. Afterwards, the particulars in the consignment note are examined one by one. Then, the evidentiary power of the consignment note is explained in detail. Although the problems of proof are subject to lex fori in cases where there is an element of foreignness, there are special rules of proof regarding the evidentiary power of the consignment note used in international transportation. For this reason, the evidentiary power of the consignment note has been discussed comparatively in terms of both national and international transportation. The study also focuses on the responsibilities arising from the consignment note, because in addition to providing proof, the consignment note may also create some responsibilities for the carrier, sender and consignee.
Consignment note within the scope of Turkish commercial code (TCC) and CMR
Keywords: consignment note; contract of carriage; Highway law; ispat aracı Road transportation; Karayolu hukuku; Karayolu taşımacılığı; Law and legislation; means of proof; taşıma senedi; taşıma sözleşmesi; Transportation; Türkiye; Ulaştırma; Yasa ve yasama